Internalization of Religious Moderation Values Through Digital Literacy at Madrasah - Ni'mah, Nilnan; Fitri, Fitri; Adlan, Imam (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2024)
The teachings of Rahmatan Lil Alamin Islam held by Muslims should also be instilled early, especially at the age of children. The social environment with diverse ethnicities, races, cultures and religions requires educators at the Madrasah Tsanawiyah (MTs) level to be present in providing moderate religious insights. Especially in the era of advances in communication technology, intolarance issues are also prone to be found on various social or digital media platforms. Therefore, religious moderations must be introduced and internalised to students. This article aims to explain the internalisation of religious moderation values through digital literacy at MTs PSM Randublatung Blora. This research is a descriptive qualitative field research, with data collection techniques of observation, interview, and documentation. The field data was analysed with descriptive qualitative method. The results of this study reveal that the internalisation of religious moderation is carried out with a class mentoring model and digital literacy training. Class mentoring to students as an effort to introduce and understand students related to religious moderation, followed by digital literacy training as an internalisation effort with students' ability to filter intolerant messages, and hate speech and be able to campaign with positive content containing religious moderation values.